Azido-meta-hemipinic Acid: An "Introverted" Acid? - Jin-Young, Choi; Jisoo, Kim; Jinyong, Shin; Minsu, Lee; Tae-Ho, Yoon; Sunmook, Lee (My University, 2018)
Biocomposite materials consisting of Poly-L-Lactic-Co-Glycolic Acid (PLGA) and Hydroxyapatite (HA) were synthesized and mechanical properties have been observed by carrying out the fatigue test, for which accelerated tests have been conducted such that 20%, 30% and 40% of the yield strength have been applied in a repeated mode until a crack occurred on the load-applied points of test specimen. Based on the fatigue test results, the lifetime of test specimen (B10 life) was estimated. It was found that Weibull distribution (shape parameter=8.79) was the most proper one to describe the failure data obtained from the accelerated fatigue tests. B10 life at 5% of yield strength was estimated to be 335,764 cycles (Confidence Level=95%, lower limit) by applying an inverse power model.
Keywords: Fatigue test; Lifetime assessment; Implantable; Biocomposite; Reliability